Dynamics of digital servitisation transformation in earthmoving equipment dealerships - Darko, Simon Yaw Osei (University of the Witwatersrand, Johannesburg, 2024)
In the rapidly evolving earthmoving equipment industry, this study investigates the challenges and opportunities stemming from digital servitization transformation. As conventional dealership models face disruption from digital technologies, the necessity for adaptation to maintain competitiveness becomes evident. This research seeks to address the gaps in understanding regarding the transformation process and the implications of digital servitisation within this industry context. Drawing upon a conceptual framework that integrates principles of digital transformation and servitisation, the study examines the critical stages of transformation and the pivotal role of leadership. Qualitative methods, including interviews with 9 senior managers and executives from two earthmoving equipment dealerships, were employed to capture insights into the transformation journey, challenges encountered, and the leadership dynamics driving the process. Key findings underscore the multifaceted nature of digital servitization transformation, emphasizing the importance of strategic alignment, IT transformation, process digitization, organizational change, customer service innovation through artificial intelligence and machine learning and leadership adaptability. The research offers a structured framework to assist industry practitioners in effectively navigating the transformation journey. In conclusion, this study emphasizes the imperative for earthmoving equipment dealerships to embrace digital servitization as a strategic imperative for long-term viability. By providing actionable insights and guidance, the research advocates for proactive adaptation to capitalize on the opportunities presented by digital technologies, thereby ensuring sustainable growth and competitiveness in the digital era
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Servitisation; Digital transformation; Digital servitisation; Digital servitisation transformation; Digital leadership; UCTD; SDG-9: Industry, innovation and infrastructure